An industry survey on screw press system in palm oil mill: operational data & malfunction issues - Harun, Mohd Yusof; Che Yunus, Mohd Azizi; Morad, Noor Azian; Shah Ismail, Mohd Halim (Elsevier, 2015)
Research questionnaires were disseminated to active palm oil mills across Malaysia to acquire information on (i) the mill operation, and (ii) the malfunction issue of screw press system. 105 mills had responded to the survey (response rate = 25%). Relationship between the mill operational data (processing capacity, daily operation cycle), the screw press system (type, quantity), and the malfunction frequency was examined. Double screw press dominated the palm oil milling industries because of its larger capacity that entails shorter processing time in comparison to the single screw press. Recurring malfunction problems are prevalence in both of the screw press systems. While fatigue, corrosion, wear and tear are inevitable due to the heavy usage and natural cause; irregular maintenance schedule and poor handling has top the list of common cause for malfunction of the screw press.